Increased levels of S100A8/A9, IL-1ß and IL-18 as a novel biomarker for recurrent tonsillitis - Christoph Spiekermann; Alicia Seethaler; Annika McNally; Markus Stenner; Claudia Rudack; Johannes Roth; Thomas Vogl (BMC, 2021)
Abstract Background Acute tonsillitis represents one of the most frequent reasons patients seek primary medical care and otorhinolaryngology consultation. Therefore, recurrent episodes of acute tonsillitis (RAT), also called chronic tonsillitis, exhaust a substantial amount of medical and financial resources. Diagnosis of tonsillitis depends on a physical examination, which therefore does not allow for a reliable differentiation between viral and bacterial infection. However, the frequency of bacterial infections during the previous three years is currently being used as the major deciding factor in patient selection for tonsillectomy. The aim of the present study was to determine an objective biomarker to help in the identification of patients suffering from recurrent tonsillitis. Results By analyzing a panel of cytokines and chemokines in serum and saliva of patients with RAT compared to healthy controls, increased levels of IL-1ß (153.7 ± 48.5 pg/ml vs 23.3 ± 6.6 pg/ml, p = 0.021), IL-18 (120.2 ± 16.5 vs 50.6 ± 9.3 pg/ml, p = 0.007) and/or S100A8/A9 (996 ± 102 ng/ml vs 546 ± 86 ng/ml, p = 0.042) could be observed in patients suffering from RAT. Cut-off values of these parameters were determined and combined to a new RAT-score allowing for reliable identification of patients suffering from recurrent tonsillitis with a sensitivity of 95% and a specificity of 88%. Conclusion The RAT-score represents the first objective criterion as a tool for the diagnosis of recurrent tonsillitis and it also improves patient selection for tonsillectomy.